Electrostatic interplay: The interaction triangle of polyamines, silicic acid, and phosphate studied through turbidity measurements, silicomolybdic acid test, and 29Si NMR spectroscopy - Jantschke, Anne; Spinde, Katrin; Brunner, Eike (Beilstein Journal of Nanotechnology, 2014)
The discovery of long-chain polyamines as biomolecules that are tightly associated to biosilica in diatom cell walls has inspired numerous in vitro studies aiming to characterize polyamine–silica interactions. The determination of these interactions at the molecular level is of fundamental interest on one hand for the understanding of cell wall biogenesis in diatoms and on the other hand for designing bioinspired materials synthesis approaches. The present contribution deals with the influence of amines and polyamines upon the initial self-assembly processes taking place during polyamine-mediated silica formation in solution. The influence of phosphate upon these processes is studied. For this purpose, sodium metasilicate solutions containing additives such as polyallylamine, allylamine and others in the presence/absence of phosphate were investigated. The analyses are based mainly on turbidity measurements yielding information about the early aggregation steps which finally give rise to the formation and precipitation of silica.
Keywords: phosphate; self-assembly; silica–polyamine interactions; silicomolybdic acid test; 29Si NMR; turbidity measurements